Uwarunkowania epistemologiczne obrazowania rzeczywistości politycznej w mediach - Kowalczyk, Ryszard (Przegląd Politologiczny, 2018)
The author reflects on the issue of epistemological limitations in the process of media imaginings of political reality. Using reference theory and description theory the author tries to answer the question of what makes up the image of political reality as verbalized in media coverage. His conclusion is that attempts to reflect the factual image in the media presentation of politics produce a specific politico-journalistic construction of this reality, the apparent reality. Therefore, the category of truth in media communications concerning the field of poli- tics usually fails. One should thus expect that this traditional realism, which is expressed on the one hand by the factual nature of the media, and on the other by the morality of the media, will constitute a pillar that supports the image of political reality that is presented, interpreted and commented on in the media. In principle, this should not be a naïve realism, giving priority to individual cognitive spontaneity rather than to reflection, analysis and experience, or a spiritual realism seeking the truth about reality through human spirituality.